A Survey of Antibiotic Usage Characteristics in Treatment of Acute Exacerbation of COPD Patients in National Hospital 74 - Bach, Tran Xuan; Trung, Tran Thanh; Son Nhat, Bui; Luyen, Le Thi (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 38 No 2DO - 10.25073/2588-1132/vnumps.4408, 2022)
Acute exacerbation of COPD (AECOPD) represents a pivotal point in the progression of COPD, which is a major cause of physician visits, hospitalization, and death in COPD patients. Bacterial respiratory infections have long been considered the main cause of exacerbations. This study was conducted with the aim of surveying the antibiotic usage characteristics in AECOPD of hospitalized patients at National Hospital 74. Data were collected from 265 patients hospitalized from January 1 st , 2021 to March 31 st , 2021. Most of the patients in the study were male (82.3%) and had comorbidities (74.7%). The most isolated bacteria were Haemophilus influenzae, Moraxella catarrhalis, and Pseudomonas aeruginosa. The majority of patients did not change their antibiotic regimen during treatment (61.5%). Alternative regimens in patients having regimen changes tended to be more focused on Pseudomonas aeruginosa than the first regimens. In the antibiotic-containing regimens tested antibiograms of 38 patients with isolated bacteria, most of the regimens had at least 1 antibiotic sensitive to the isolated bacteria (38.5%). The results of this study provide reliable information for making recommendations to contribute to improving the effectiveness of antibiotic usage in the AECOPD treatment at National Hospital 74, reducing the medical burden for patients and society.